Knowledge and Behaviors Toward Health Care for Elderly Patients with Hypertension, and Quality of Life Among Informal Caregivers in Northern Thailand - Seangpraw, Katekaew (J Multidiscip Healthc, 2020)
BACKGROUND: Informal caregivers play an important role in caring for patients with chronic conditions. Little is known about the quality of life among caregivers of patients with chronic illnesses in Thailand. The purpose of this study was to investigate the relationships among knowledge and behaviors toward health care for elderly patients with hypertension, and the quality of life among informal caregivers. METHODS: A total of 402 informal caregivers for their elderly co-habitants suffering from hypertension were randomly selected to participate in this cross-sectional study. Data collection was performed in rural areas of Phayao province, located in the northern part of Thailand. Self-administered questionnaires were employed, which covered knowledge and behaviors toward health care for elderly patients with hypertension, and the Thai version of the World Health Organization Quality of Life Brief Version (WHOQOL-BREF) questionnaire. RESULTS: The scores of knowledge and behaviors toward health care for elderly patients with hypertension, and the quality of life were at low and fair levels. In the multivariable linear regression model, the results showed that four variables – age, caregiver’s relationship to the patient, knowledge, and behaviors toward health care for elderly patients with hypertension – were significantly related to quality of life among caregivers (p < 0.05). CONCLUSION: Knowledge and behaviors toward health care for hypertensive patients influence the quality of life among informal caregivers. The caregivers in rural communities should be encouraged to become educated on the stages of hypertension, preparation for taking care of the elderly with high blood pressure, and effective behavioral care for patients, in order to improve the quality of life of both caregiver and patient. In addition, health care providers should have clear guidelines for development of the health care system to enhance the potential care and quality of life among informal caregivers.